1991
DOI: 10.1111/j.1752-7325.1991.tb02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Time to Adoption of an Innovation by Dentists in Private Practice: Sealant Utilization

Abstract: Dentists can be divided into five adoption categories based upon their time of adoption of pit and fissure sealants: innovators, early adopters, early majority, late majority, and laggards. The differences among dentists in the five adoption categories were examined for four classes of variables: practice characteristics, dentist characteristics, communication of information, and practice environment. Questionnaires were mailed in September 1984 to a random sample (N = 521) of Washington State dentists in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…38,42,43 The decision to integrate change into dental practice has not been well studied, but several sources indicate that change may occur most readily through collegial friendships and dental society meetings. 38,42,50,51 Thus, dental societies may be effective in changing their members’ practice behavior with respect to promotion of water fluoridation.…”
Section: Injecting Change Into Clinical Dentistrymentioning
confidence: 99%
“…38,42,43 The decision to integrate change into dental practice has not been well studied, but several sources indicate that change may occur most readily through collegial friendships and dental society meetings. 38,42,50,51 Thus, dental societies may be effective in changing their members’ practice behavior with respect to promotion of water fluoridation.…”
Section: Injecting Change Into Clinical Dentistrymentioning
confidence: 99%
“…[14][15][16][17] Finally, the practice environment and other organisational factors such as degree of delegation to team members have been related to the adoption of specific practices. 18,19 The objective of this study was to measure the extent and nature of recent self-reported change in a sample of English GDPs. In addition factors influencing change were also assessed.…”
Section: N B R I E Fmentioning
confidence: 99%
“…Since pit and fissure sealants became readily available in the early 1970s, their use by dentists has been the subject of several studies and published reports (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), editorials , and letters to the editor (15)(16)(17), as well as conferences and symposia (18-21).…”
mentioning
confidence: 99%